Strategi Manajemen Keuangan untuk Bisnis Startup - David Yenaldi; Dewi Sartika; Tri Yuli Astuti; Toha Bukhori Simatupang (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2025)
This research examines effective financial management strategies for startup Businesses, with a focus on the importance of proper financial planning and Management in supporting the success of new businesses in the competitive Digital economy era. The study in this research uses literature. The research Results show that an effective financial management strategy for startups Includes several key aspects, including: realistic and flexible financial planning, Strict cash flow management, diversification of funding sources, optimization Of capital structure, efficient cost control, as well as implementation of an Accounting system and accurate financial reporting. The research findings also Emphasize the importance of startups adopting an adaptive approach to Financial management, given the rapidly changing market dynamics. Strategies Such as bootstrapping, lean startup methodology, and the use of financial Technology (fintech) to automate financial processes were found to be Effective practices in optimizing limited financial resource.